Well-Being Status of Tribals Dependenton Shifting Cultivation in Dhalai, Tripura - D.K. Pandey , H.K. De , P. Adhiguru and Mahesh Pathak (Indian Journal of Extension Education, 2018)
This study provides an important empirical insight into well-being status of hill people of Dhalai, a remotehill district of Tripura, North Eastern Region (NER) of India whose livelihood primarily depends on ShiftingCultivation (SC). Using a resilience approach, 50 tribal households were interviewed with the help of structuredinterview schedule. With regard to psychological well-being, about 92% households has perceived it to bemoderate or inconsistent and are experiencing difficulties as on date and is expected to continue with it in thenear future. In case of economic well-being, 86%households were under poverty trap with high incomeinequality. Findings also revealed transition in terms of aversion of tribal youths to SC, declining dependencyon SC, overdependence on Non-Timber Forest Produces, higher inclination towards settled cultivation withpreferences for high value horticultural crops. Food security was found ensured among hill people and significantproportion of total expenditure was devoted on education & health.The authors suggest that the policy andpolitical alternatives of mainstream prescriptions for hill people in Dhalaiwhich has hitherto focused on thenarrow issue of shifting to settled cultivation should shift its emphasis to diversification of economic activitiesin the tribal regions for improving people’s well-being and natural resource management,